Chandipura Virus Induced Neuronal Apoptosis via Calcium Signaling Mediated Oxidative Stress - Verma, Abhishek K.; Ghosh, Sourish; Basu, Anirban (Frontiers in Microbiology, 2018)
Chandipura Virus (CHPV) a negative-stranded RNA virus belonging to the Rhabdovirdae family, has been previously reported to bring about neuronal apoptosis by stimulating oxidative stress. Our in silico data suggested the involvement of Angiotensin II in intracellular Ca2+ secretion within CHPV infected cells that further lead to enhancement of ROS level and mitochondrial dysfunction. ROS is also known to phosphorylate p38 that leads to neuronal apoptosis through FasL-FADD pathway during CHPV infection. Minocycline a broad-spectrum antibiotic well-known for its anti-oxidative and anti-inflammatory role was used in the present study to investigate its efficacy against CHPV. The results obtained from the present study showed minocycline to be effective in mitigating the levels of cytoplasmic Ca2+, ROS, phosphorylation of p38 molecules and hence cellular apoptosis. Thus minocycline apart from being an anti-inflammatory and anti-oxidative agent, our study showed that minocycline has an additional Ca2+ chelation activity.